The Concept of a Country According To Thought Ibn Bājjah in The Book Tadbīr Al-Mutawaḥḥid: Konsep Negara Menurut Pemikiran Ibn Bājjah Dalam Kitab Tadbīr Al-Mutawaḥḥid - Januarti, Putri; Lestari, Ayu; al-Walid, Khalid (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2024)
The role of the state in politics is a very complex and interesting issue, especially because the concept of the state has varied meanings and interpretations among experts. Ibn Bājjah, also known as Avempace, was a Muslim philosopher and scientist from western Andalusia who lived in the 11th century. His contribution to Islamic political thought is mainly reflected in his work entitled "Tadbīr al-Mutawaḥḥid". In this work, Ibn Bājjah examines the concept of the state in two main categories: the perfect (ideal) state and the imperfect state. The aim of this research is to understand the concept of the state according to Ibn Bājjah's thoughts in the book "Tadbīr al-Mutawaḥḥid" so that it can serve as an inspiration from classical thinking to be applied in a modern context. This research uses a qualitative research model with a descriptive analytical library research approach. The conclusion of this research shows Ibn Bājjah's view of perfect and imperfect states. According to him, a perfect state is one that does not need doctors and judges because there are no conflicts, diseases, or legal problems. On the other hand, imperfect states need doctors (the art of medicine) and judges (the art of law) because there are still conflicts, diseases, and differences of opinion in society.